Penerapan Green Accounting dalam Pengelolaan Limbah Medis Pada RSUD Labuang Baji Makassar - Fadilah Yusriyah Bestari; Baso Amang; Asri Ady Bakri (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
ABSTRACT This study aimed to analyze the implementation of green accounting in medical waste management at Labuang Baji Regional General Hospital, identify the challenges encountered, and formulate strategies to improve medical waste management based on green accounting principles. This study employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation involving informants responsible for medical waste management and hospital financial management. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. The results show that medical waste management at Labuang Baji Regional General Hospital has been implemented in accordance with standard operating procedures and applicable regulations, covering waste segregation, temporary storage, transportation, and final disposal. However, green accounting has not been fully implemented because environmental management costs are still recorded as part of general operational expenses, without separate recognition and disclosure of environmental costs. The main challenges include the absence of separate environmental cost accounting, constraints in waste manifest reporting, dependence on third-party service providers for medical waste disposal, and the suboptimal implementation of standard operating procedures. Based on these findings, the proposed strategies include developing an environmental accounting system, separately recording environmental costs, optimizing the waste reporting system, strengthening compliance with standard operating procedures, and improving interdepartmental coordination. In conclusion, strengthening the implementation of green accounting is essential to enhance the transparency, accountability, and sustainability of medical waste management at Labuang Baji Regional General Hospital. Keywords:green accounting, medical waste management, hospital, environmental costs, environmental accounting.